Detection of AdeAB, TetA, and TetB efflux pump genes in clinical isolates of tetracycline-resistant Acinetobacter baumannii from patients of Suez Canal University Hospitals - Hasnaa Azab; Aya Mohamed Askar; Noha M. Abd El-Fadeal; Amira A. A. Othman; Amal H. Rayan; Sally Khattab (BMC Microbiology)
Abstract Background Acinetobacter baumannii is an opportunistic bacteria associated primarily with hospital-acquired infections. Its tendency to acquire or donate resistance genes to neighboring bacteria is a major concern. Tetracyclines have shown promise in treating A. baumannii infections, but tetracycline resistance is growing globally in A. baumannii isolates. Objectives The study aimed to study (1) the prevalence of multidrug-resistant (MDR) A. baumannii infections at Suez Canal University Hospitals, (2) the distribution of efflux pump genes AdeA &B, TetA, and TetB, and (3) the effect of efflux pump inhibitor (CCCP) on tetracycline-resistant isolates. Methods Clinical samples (457) were collected (blood, urine, sputum, ETA, pus, and pleural fluid), followed by A. baumannii isolation and identification, PCR detection of efflux pump genes, and detection of tetracycline susceptibility and its MIC before and after treatment with the efflux pump inhibitor (CCCP). Results A total of 31 A. baumannii isolates were recovered (6.78%). The highest rate of isolation was from the ICU (48.3%) from the ET aspirate samples (48.3%). The efflux system AdeA and TetB genes were distributed in 100% of isolates, whereas AdeB was found in 93.5% of isolates and the TetA gene in 87.1% of isolates. All A. baumannii isolates were MDR showing resistance to three or more classes of antibiotics. 45% of the isolates showed a 4-fold reduction of MIC and 12.9% showed a 2-fold reduction in the MIC. Conclusions Efflux pump is an important mechanism for tetracycline resistance among A. baumannii isolates.